Acute Changes in Creatine Kinase Serum Levels in Adults Submitted a Static Flexibilizing and Maximal Strength Test - E. Peixoto; M. E. Palacio; M. G. Bara; J. R. Perrout; L. Conte; E. H. Dantas (Asociación Española de Ciencias del Deporte, 2010)
ABSTRACT Strength and flexibility, important components of a training and their maximal values are obtained through specific tests. However, little information about the damage effect in a skeletal muscle is known. The aim was to verify a serum CK changes 24 h after a lengthening and static flexibilizing routine and a maximal dynamic strength tests. The sample, was by 14 subjects (man and women, 28 ± 6 yr.), control group (CG N = 7) and experimental group (EG N = 4) that was submitted a lengthening routine (EG-LG), a static flexibilizing routine (EG-FLEX) and a 1-RM test (EG-1-RM). The anthropometrics were obtained by digital scale with stadiometer. The blood samples were obtained using the IFCC method with reference values 26-155 U/L. The De Lorme and Watkins technique was used to access maximal dynamic strength through bench press and leg press. The static flexibilizing routine consisted in three 20 seconds sets until the point of maximal discomfort. The lengthening was done in normal movement amplitude during 6 seconds. In analysis inter groups was a significant difference (p < .05) in the values of GE-1RM (D = 118,7 U/L, p= .02) when compared to the GC. We concluded that only maximal strength dynamic test was capable to raise the CK serum levels 24 h after exercise Key Words: Lengthening, Static Flexibilizing, 1-RM, Creatine Kinase